(untitled) (Baghdad Science Journal, 2013)
A total of 54 out of 67 (80.59%) of burn wound swab showed growth of one, or two, or three bacterial pathogens. Pseudomonas aeruginosa was the commonest pathogen, isolated in 48.14% of swab samples, followed by Klebsiella pneumoniae (31.48%), Staphylococcus aureus (27.77%), Acinetobacter baumanii (14.81%), Escherichia coli (7.40%), and Citrobacter freundii, Providencia stuartii, Enterobacter cloacae, with 1.85% isolation percentage for each. All bacterial isolates were tested against 19 antibiotics, and showed multi-drug resistance to 10 antibiotics, or more. The most effective antibiotics were the fifth-generation cephalosporin, ceftobiprole, and and antibiotic combinations, as Ceftazidime / clavulanic acid, and Cefoperazone /sulbactam, and newer generation fluoroquinolone, levofloxacin, and gemifloxacin, which are attractive candidates to be the basic antibiotics in establishment of new hospital policy in Iraq for treatment of burn wound infection of multi-drug resistant bacteria